The determinants of livestock prices in Niger - Fafchamps, M.; Gavian, S. (1997)
Not only does livestock make an important contribution to rural incomes and export earnings in the Sahel, it is also kept as insurance against weather risk. Fluctuations in livestock prices can therefore trigger food entitlement failures. Using monthly price data from Niger, we show that livestock prices respond to droughts and pasture availability. They are also exposed to aggregate shifts in export revenues and meat demand that affect Niger and Its southern neighbour, Nigeria. These shifts add an important element of risk to the livelihood of Sahelian farmers and pastoralists. Famine early-wearning systems should keep an eye not only on weather shocks but also on macroeconomic conditions and other factors affecting the livestock economy. It is showed in this paper that livestock prices in Niger, a representative Sahelian country, respond not only to weather shocks but also to shifts in the rural and urban demand for meat in the country and in neighbouring Nigeria. The basis for the analysis is price data on 15 animal categories collected monthly in 38 districts of Niger over a period of 21 years. The questionable quality of the data and the high proportion of missing observations are compensated by the sheer number of data points: 87,000 in total. This data is complemented with monthly rainfall by district and published statistics on mineral exports and cereal production.